2022
DOI: 10.1111/mmi.14873
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Trypanosoma brucei as early procyclic forms and social motility are dependent on glycosylphosphatidylinositol transamidase

Abstract: As the primary interface between a cell and its environment, surface components of the plasma membrane mediate direct contact, perception of external cues and release of signalling molecules, while acting as a barrier that allows binding, uptake and secretion of diverse classes of substances. For pathogenic organisms, the functional integrity and composition of the cell surface impacts their virulence, infectivity and transmission (recently reviewed in de Castro Neto et al., 2021). GPI-anchored glycoproteins a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Using a conditional overexpression of the GPI-transamidase complex subunit TbGPI8 in a null mutant background, it was found that the abolition of processing and transport of GPI-anchored proteins was accompanied by differentiation from early to late PCFs and loss of SoMo in vitro. It has been demonstrated that neither EP nor GPEET procyclin are essential for SoMo, and therefore it remains to be seen which GPI-anchored protein/proteins is/are required [65,80].…”
Section: Somomentioning
confidence: 99%
See 1 more Smart Citation
“…Using a conditional overexpression of the GPI-transamidase complex subunit TbGPI8 in a null mutant background, it was found that the abolition of processing and transport of GPI-anchored proteins was accompanied by differentiation from early to late PCFs and loss of SoMo in vitro. It has been demonstrated that neither EP nor GPEET procyclin are essential for SoMo, and therefore it remains to be seen which GPI-anchored protein/proteins is/are required [65,80].…”
Section: Somomentioning
confidence: 99%
“…In addition to the above mentioned SoMo components, it has also been recently described that GPI-linked surface proteins are mediators of SoMo and developmental progression [ 80 ]. Using a conditional overexpression of the GPI–transamidase complex subunit Tb GPI8 in a null mutant background, it was found that the abolition of processing and transport of GPI-anchored proteins was accompanied by differentiation from early to late PCFs and loss of SoMo in vitro .…”
Section: Somomentioning
confidence: 99%